2017
DOI: 10.1038/s41598-017-06612-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sofosbuvir (β-D-2′-deoxy-2′-α-fluoro-2′-β-C-methyluridine) as an inhibitor of Dengue virus replication #

Abstract: We evaluated Sofosbuvir (SOF), the anti-hepatitis C virus prodrug of β-d-2′-deoxy-2′-α-fluoro-2′-β-C-methyluridine-5′-monophosphate, for potential inhibitory activity against DENV replication. Both cell-based and biochemical assays, based on use of purified DENV full-length NS5 enzyme, were studied. Cytopathic effect protection and virus yield reduction assays confirmed that SOF possessed anti-DENV activity in cell culture with a 50% effective concentration (EC50) of 4.9 µM and 1.4 µM respectively. Real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 54 publications
4
61
0
1
Order By: Relevance
“…Considering that these agents belong to the same family of viruses, it was plausible to test sofosbuvir against YFV.Indeed, we observed that sofosbuvir predictively targets the YFV RNA RNA polymerase in silico and by dose response antiviral assays. In fact, the in vitro antiviral results display that sofosbuvir`s EC50% towards YFV is in micromolar range and comparable to what has been described for ZIKV and DENV (9)(10)(11). Sofosbuvir`s metabolism is complex and some facets are clearly undescribed.…”
Section: -Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Considering that these agents belong to the same family of viruses, it was plausible to test sofosbuvir against YFV.Indeed, we observed that sofosbuvir predictively targets the YFV RNA RNA polymerase in silico and by dose response antiviral assays. In fact, the in vitro antiviral results display that sofosbuvir`s EC50% towards YFV is in micromolar range and comparable to what has been described for ZIKV and DENV (9)(10)(11). Sofosbuvir`s metabolism is complex and some facets are clearly undescribed.…”
Section: -Discussionmentioning
confidence: 67%
“…Several groups demonstrated that the clinically approved anti-HCV drug sofosbuvir is endowed with antiviral activity towards other flavivirus such as ZIKV (9, 10) and DENV (11). Considering that these agents belong to the same family of viruses, it was plausible to test sofosbuvir against YFV.Indeed, we observed that sofosbuvir predictively targets the YFV RNA RNA polymerase in silico and by dose response antiviral assays.…”
Section: -Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It has been found that HCV and ZIKV RNA polymerases have very similar active sites, confirming that sofosbuvir could also act on ZIKV-infected cells. It was also demonstrated via cellular assays and animal models that sofosbuvir inhibits the replication of other flaviviruses, such as dengue virus (DENV) (Xu et al, 2017), yellow fever virus (YFV) , and chikungunya virus (CHIKV) .…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have demonstrated that sofosbuvir, a clinically approved against hepatitis C virus (HCV) (11-13), also inhibits the replication of flaviviruses, like ZIKV, DENV and yellow fever virus (YFV) (14-19). Sofosbuvir is a safe and a well-tolerated drug, from 400 to 1200 mg daily in 24 weeks regimen.…”
Section: Introductionmentioning
confidence: 99%